2011
DOI: 10.1038/gene.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

IL-23R rs11209026 polymorphism modulates IL-17A expression in patients with rheumatoid arthritis

Abstract: The interleukin (IL)-17/IL-23 axis is an important pro-inflammatory pathway in rheumatoid arthritis (RA). IL-23 maintains CD4 þ T-helper 17 (Th 17 ) cells, whereas IL-12 negates IL-17A production by promoting Th 1 -cell differentiation. We sought evidence for any effect of polymorphisms within the interleukin-23 receptor (IL-23R), IL-12 or IL-21 genes on serum cytokine concentrations in 81 patients with RA. Serum cytokines were measured using bead-based multiplex assays. Targeted cytokines were detected in up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 42 publications
3
33
2
Order By: Relevance
“…Those results suggest that IL-23 receptor AA genotype variant of rs11209026 would contribute to RA etiology; consequently, it might be a genetic marker for RA. Another study reported that a R381Q polymorphism modulated IL-17A expression in patients with RA (Hazlett et al 2012). Those authors suggested that, in patients with the 381Gln allele, higher IL-23 concentrations might have been needed to produce IL-17A concentrations similar to those in patients with a 381Arg allele.…”
Section: Role For R381q Variant In Non-gastrointestinal Autoimmune DImentioning
confidence: 96%
“…Those results suggest that IL-23 receptor AA genotype variant of rs11209026 would contribute to RA etiology; consequently, it might be a genetic marker for RA. Another study reported that a R381Q polymorphism modulated IL-17A expression in patients with RA (Hazlett et al 2012). Those authors suggested that, in patients with the 381Gln allele, higher IL-23 concentrations might have been needed to produce IL-17A concentrations similar to those in patients with a 381Arg allele.…”
Section: Role For R381q Variant In Non-gastrointestinal Autoimmune DImentioning
confidence: 96%
“…This could be a reflection of diverse pathomechanisms in SLE and RA. The up-regulation of IL-17A together with unaltered IL-2 expression in RA could be a result of increased Stat3 activation through IL-6 or attenuated IL-23 receptor signaling in the absence of increased CREMα expression (20). (iii) We document a mechanism that contributes to T-cell lineage determination and an enrichment of effector memory phenotypes in SLE.…”
mentioning
confidence: 95%
“…Thus, we examined the mRNA expression of CREMα, IL-2 and IL-17A, and CpG-DNA methylation of the promoters of CREM, IL2, and IL17A in T cells from SLE patients with active (SLEDAI: 8-14) and inactive (SLEDAI: 0-4) disease vs. age-, sex-, and ethnicity-matched healthy controls (Table S1). Because patients with RA produce increased levels of proinflammatory cytokines, including IL-2 (5,19,20), we included T cells from RA patients with active disease in our study (Table S2, Fig. S4).…”
Section: Crem Promoter P1 Activity Is Controlled By Cpg-dna Methylationmentioning
confidence: 99%
“…Some studies also indicated that the A allele frequency of R381Q was lower in ankylosing spondylitis (AS) patients than in healthy controls (Duan et al, 2012;Rahman et al, 2008). Another study indicated that a R381Q polymorphism modulated IL-17A expression in patients with rheumatoid arthritis (Hazlett et al, 2012). Those authors suggest that, in patients with the 381Gln allele, higher IL-23 concentrations may be needed to produce IL-17A concentrations similar to those in patients with the 381Arg allele.…”
Section: Discussionmentioning
confidence: 93%